2022
DOI: 10.1093/rheumatology/keac036
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immunogenicity of COVID-19 vaccines in patients with inflammatory rheumatic diseases under treatment with Rituximab: a case–control study (COVID-19VacRTX)

Abstract: Objectives Patients with inflammatory rheumatic diseases (IRD) treated with the monoclonal anti-CD20 antibody rituximab (RTX) have been identified as high-risk for severe COVID-19 outcomes. Additionally, there is increased risk due to reduced humoral immune response, induced by therapeutic B cell depletion. This study sought to quantify humoral response after vaccination against SARS-CoV-2 in patients with IRD treated with RTX. It also sought to elucidate the influence of timeframe between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
4
6
0
Order By: Relevance
“…Experts suggest waiting at least five months after the last rituximab administration (21,22). Our study, corresponding to others, found that vaccinating at less than six months post-rituximab is extremely low yielded since the humoral immune response to COVID-19 vaccines was virtually blocked by rituximab during this period (42)(43)(44)(45). IMDD patients who required rituximab every six months should be considered for alternative COVID-19 preventive measures, for instance, passive immunization with Tixagevimab/Cilgavimab injection (i.e., human monoclonal antibodies against the surface spike protein of SARS-CoV-2).…”
Section: Discussionsupporting
confidence: 67%
“…Experts suggest waiting at least five months after the last rituximab administration (21,22). Our study, corresponding to others, found that vaccinating at less than six months post-rituximab is extremely low yielded since the humoral immune response to COVID-19 vaccines was virtually blocked by rituximab during this period (42)(43)(44)(45). IMDD patients who required rituximab every six months should be considered for alternative COVID-19 preventive measures, for instance, passive immunization with Tixagevimab/Cilgavimab injection (i.e., human monoclonal antibodies against the surface spike protein of SARS-CoV-2).…”
Section: Discussionsupporting
confidence: 67%
“…In this cohort, a high vaccination rate and a low infection rate were observed during the first 11 months of the study period. 7,8 COVID-19 vaccines do generate anti-S1 IgG, [22][23][24] and a significant association between the anti-S1 IgG levels and infection risk reduction was observed in this study. In the prediction model, values above 900 BAU/mL added little to the infection risk reduction in the pre-Omicron period.…”
Section: Discussionsupporting
confidence: 63%
“…B-cell-targeted therapies are the cornerstone of treatment for many systemic autoimmune diseases, and they often represent non-deferrable treatment for some clinical conditions. It has been suggested that B-cell recovery before vaccination increases the chances of an adequate humoral response to the vaccine [ 29 ]. However, our results indicate that B-cell depletion cannot preclude SARS-CoV-2 vaccination, since a cellular immune response can be elicited even in the absence of circulating B cells.…”
Section: Discussionmentioning
confidence: 99%